Pengaruh Profesionalisme Guru Dan Fasilitas Belajar Terhadap Mutu Pendidikan Di SMP Negeri Se Kecamatan Talang Kelapa - Endah Yuniarti; Tri Widayatsih; Mahasir Mahasir (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This research aims to determine the influence of teacher professionalism and learning facilities on the quality of education in State Middle Schools in Talang Kelapa District. Teacher professionalism is measured through teacher pedagogical, personality, social and professional competencies, while learning facilities include facilities and infrastructure that support the learning process in schools. This research uses a quantitative method with a survey approach, involving a sample of teachers and students in State Middle Schools throughout Talang Kelapa District. The data analysis technique used is multiple linear regression to test the influence of independent variables on the quality of education. The research results show that teacher professionalism and learning facilities have a positive and significant influence on the quality of education. This indicates that increasing teacher professionalism and providing adequate learning facilities can improve the quality of education in schools. Therefore, it is hoped that there will be improvements in these two aspects in order to achieve better quality education in State Middle Schools throughout Talang Kelapa District.